Investigation on heat transfer characteristics of ceramic coated piston crown for a CNGDI engines / Helmisyah Ahmad Jalaludin - Ahmad Jalaludin, Helmisyah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
High temperature and pressure produced in an engine of compressed natural gas with direct injection system (CNGDI) may lead to high thermal stresses. With less proper heat transfer, the piston crown material fails to withstand high temperature and operate effectively. By insulating the surface namely; thermal barrier coating (TBC) such as ceramic based yttria partially stabilized zirconia (YPSZ), heat transfer to the piston might be reduced and lead to improvement of piston durability. Hence, in this research, YPSZ coating was utilised to differentiate between the uncoated and conventional tin-coated piston crowns in terms of the ability to reduce thermal stresses on the piston. Several samples of ACS A aluminium alloy piston crowns were coated with bonding element of NiCrAl and Zr02~7.5Y203 namely the YPSZ as the top coat by using plasma spraying technique. The coating surfaces were assessed on their microstructure, surface roughness, hardness, and burner rig test. The rig test showed that a better performance of the YPSZ/NiCrAl coating could withstand the tests. The burner rig test exhibited a higher temperature difference of the YPSZ/NiCrAl coated piston crown than the other piston crowns. The heat flux for the YPSZ/ NiCrAl-coated piston crown was about 98% reduction compared to the uncoated piston crown.